Modeling post-fire behavior of aluminum structural components using a maximum temperature approach. (July 2017) - Rippe, Christian; Case, Scott; Lattimer, Brian
Abstract: Aluminum alloys exhibit permanent degradation of material strength subsequent to reaching temperatures above 200 °C. While modeling of aluminum structural components during fire is becoming more heavily researched, modeling response of aluminum structures following fire events has still not been explored. Previous research suggests that the post-fire strength of AA6061 is heavily correlated to the maximum temperature reached during the fire. This research uses the maximum exposure temperature as an input to finite element simulations of a small scale aluminum beam to predict the post-fire behavior of the beam. Results of the simulations were compared to a set of post-fire thermo-mechanical experiments. Samples were heated using a radiative source, water quenched, and then loaded to failure in a four point bending configuration. The simulated thermal response of the aluminum was within 10% of measured values across the entire side of the beam. Prediction of the unexposed mechanical response was within 5% of experimentally measured response. The post-fire peak bending load from simulations generally over-predicted the experimentally measured value while predictions of the flexural stiffness were within 15% of experimental results.